Development of metacognitive skills on the implementation of EAQD-PC models-learning journals in biology learning - N. Nurmi; Herawati Susilo; I. Ibrohim; S. Suhadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Metacognitive skills are important because they help people develop an understanding of effective strategies. This skill also helps improve one's critical thinking and creative thinking so as to be able to overcome problems in everyday life. The purpose of this research is to train students' metacognitive skills through biology learning using the EAQD-PC learning model (acronym of exploring, analyzing, questioning, defining-peer coaching) which is integrated learning journals (LJ). This research was conducted at the University of Muhammadiyah Bone, South Sulawesi, Indonesia. Using a quantitative research design, 43 students were taught by EAQD-PC-LJ. Metacognitive skills were tested with an essay test three times. Previous essay tests were validated by expert raters and tested on previous batches of students to measure empirical validity and reliability. All tests are valid and reliable. The results of the treatment showed an improvement in students' metacognitive skills through three tests. The findings of this study prove that EAQD-PC-LJ is effectively used to improve students' metacognitive skills through the learning process. Learning journals have an important role as a tool to train students' mastery of concepts and knowledge.